Py-GC/MS study of lignin pyrolysis and effect of catalysts on product distribution - Zhan, Si; Chenguang, Wang; Kang, Bi; Xinghua, Zhang; Chiling, Yu; Renjie, Dong; Longlong, Ma; Changle, Pang (International Journal of Agricultural and Biological Engineering, 2017)
Fast pyrolysis is one of the most promising methods to convert lignin into fuels and chemicals. In the present study, pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) was used to evaluate vapor phase product distribution of lignin fast pyrolysis. During the non-catalytic pyrolysis process, lignin was pyrolyzed at 400°C, 500°C and 600°C respectively, finding that the highest yield of aromatic hydrocarbons was obtained at 600°C. Catalytic pyrolysis experiments were also conducted to investigate the effects of catalyst pore structure and acidity on the product distributions. Five different catalysts (HZSM-5, MCM-41, TiO2, ZrO2 and Mg(Al)O) were applied to lignin catalytic pyrolysis, and the catalytic performance was estimated by analyzing the pyrolytic products. The catalysts were characterized by using X-ray diffraction (XRD), BET, and NH3 (CO2) temperature programmed desorption. Based on these characterizations, discussion was carried out to explain the formation of the produc distributions. Among the five catalysts, HZSM-5 exhibited the best performance on the formation of aromatic hydrocarbons. Keywords: lignin, Py-GC/MS, fast pyrolysis, catalytic upgrading, pore structure, acid-base property DOI: 10.25165/j.ijabe.20171005.2852 Citation: Si Z, Wang C G, Bi K, Zhang X H, Yu C L, Dong R J, et al. Py-GC/MS study of lignin pyrolysis and effect of catalysts on product distribution. Int J Agric & Biol Eng, 2017; 10(5): 214–225.